Party. Politics.Ph Internet Campaigning in the Philippines. [article]. - Teehankee, Julio C.
This article is an initial assessment of internet utilization by political parties in the Philippines. The phenomenal growth in the use of Information Communication Technologies (ICTs) in the country is not lost to political parties, candidates, and campaign managers. Online websites and voters through information provision, transparency, interactivity, and networking. The article conducted a content analysis of the websites of five mainstream political parties and twelve party list organizations represented in the 14th Congress. It appraised the online presence of these parties and assessed the level of use of the internet as a tool for internal party administration, online electoral campaigns, voters' participation and organization. -- (from the author)